(E)-2-[4-(Diethylamino)styryl]-1-methylquinolin- 1-ium 4-chlorobenzenesulfonate monohydrate - Chantrapromma, Suchada; Kaewmanee, Narissara; Boonnak, Nawong; Ching, Kheng Quah; Fun, Hoong Kun (International Union of Crystallography, 2014)
The asymmetric unit of the title hydrated salt, C22H25N2 +·C6H4ClO3S−·H2O, comprises two 2-[4-(diethylamino)styryl]-1-methylquinolin-1-ium cations, two 4-chlorobenzenesulfonate anions and two solvent water molecules. One ethyl group of both cations displays disorder over two positions in a 0.659 (2):0.341 (2) ratio in one molecule and in a 0.501 (2):0.499 (2) ratio in the other. The sulfonate group of one anion is also disordered over two positions in a 0.893 (7):0.107 (7) ratio. The dihedral angle between the mean plane of the quinolinium ring system and that of benzene ring is 10.57 (18)° in one cation and 14.4 (2)° in the other. In the crystal, cations, anions and water molecules are linked into chains along the [010] direction by O—H⋯Osulfonate hydrogen bonds, together with weak C—H⋯Osulfonate and C—H⋯Cl interactions. The cations are stacked by π–π interactions, with centroid–centroid distances in the range 3.675 (2)–4.162 (3) Å.